Psychological mechanisms of English academic stress and academic burnout: the mediating role of rumination and moderating effect of neuroticism - Zuo, Xiaoyi; Zhao, LuLu; Li, Yue; He, Wanting; Yu, Chengfu; Wang, Zhenhai (Frontiers in Psychology, 2024)
Introduction: Academic stress is a significant and prevalent phenomenon among college students.According to the Demands-Resources Model, when individuals are unable to cope with stress that exceeds their capacity, burnout may occur. Although English courses hold a significant position in university education, there has been limited research on the mechanisms linking English academic stress to English academic burnout.Methods: This study recruited 1130 undergraduate students taking English courses. Participants completed online questionnaires assessing English academic stress, rumination, English academic burnout, and neuroticism traits. A moderated mediation model was constructed to examine the relationship among these variables.Results: The results indicate that (1) Rumination serves as a mediator in the relationship between English academic stress and burnout; (2) neuroticism significantly moderates the pathway between English academic stress and rumination. Specifically, students with high neuroticism tendencies are more prone to developing rumination when faced with high levels of English academic stress.Conclusion: These findings offer valuable insights into the psychological mechanisms underlying the association between English learning stress and academic burnout. They emphasize the importance of addressing rumination as a mediator and considering individuals' levels of neuroticism in interventions aimed at preventing and alleviating academic burnout among university students.